2017
DOI: 10.12688/f1000research.10572.1
|View full text |Cite
|
Sign up to set email alerts
|

RNA and Proteins: Mutual Respect

Abstract: Proteins and RNA are often found in ribonucleoprotein particles (RNPs), where they function in cellular processes to synthesize proteins (the ribosome), chemically modify RNAs (small nucleolar RNPs), splice pre-mRNAs (the spliceosome), and, on a larger scale, sequester RNAs, degrade them, or process them (P bodies, Cajal bodies, and nucleoli). Each RNA–protein interaction is a story in itself, as both molecules can change conformation, compete for binding sites, and regulate cellular functions. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…The authors concluded that base pairs in the RNA hairpins are progressively disrupted by stacking interactions with the aromatic side chains, accompanied by hydrogen bonding with surrounding basic residues. This combination of aromatic and basic side chains, found in other RNA binding proteins (83), seems to offer a flexible yet energetically favorable interaction surface for single-stranded RNA. Importantly, side chains on the exposed surface of CspA are dynamic (84), but are stabilized upon binding to the RNA hairpin (82).…”
Section: Introductionmentioning
confidence: 91%
“…The authors concluded that base pairs in the RNA hairpins are progressively disrupted by stacking interactions with the aromatic side chains, accompanied by hydrogen bonding with surrounding basic residues. This combination of aromatic and basic side chains, found in other RNA binding proteins (83), seems to offer a flexible yet energetically favorable interaction surface for single-stranded RNA. Importantly, side chains on the exposed surface of CspA are dynamic (84), but are stabilized upon binding to the RNA hairpin (82).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, we also observed an upregulation of snoRNAs, a type of small noncoding RNAs implicated in a broad range of biological functions including the regulation of ribosomes and of fundamental cancer proteins by directly binding to them or affecting their posttranslational modifications or their RNA molecules (43)(44)(45)(46)(47)(48). The role of snoRNAs in lymphoid neoplasms has not yet been fully explored (49,50) and they appear largely reduced in tumors compared with normal tissue counterparts (49).…”
Section: Discussionmentioning
confidence: 78%
“…The last two decades have seen the development of high-throughput gene expression profiling technologies, including DNA microarrays and RNA-sequencing (RNA-seq), leading to an increased focus on RNA and its interacting partners. Indeed, increasing numbers of RNA–protein ( 1 ), RNA–small molecule (e.g. riboswitches ( 2 )) and RNA–RNA interactions (e.g.…”
Section: Introductionmentioning
confidence: 99%